Time-resolved surface-enhanced resonance Raman spectro-electrochemistry of heme proteins. Issue 1 (2010) - Grosserueschkamp Grosserueschkamp, Marc Marc; Nowak Nowak, Christoph Christoph; Knoll Knoll, Wolfgang Wolfgang; Naumann Naumann, Renate L. C. Renate L. C.
Abstract : Heme proteins such as cytochrome c (cc) play a fundamental role in many biological processes. Surface-enhanced resonance Raman spectroscopy (SERRS) combined with electrochemical methods is an ideal tool to study the redox processes of heme proteins. In this context we designed a new measuring cell allowing for simultaneous electrochemical manipulation and high sensitive SERRS measurements of heme proteins. The measuring cell is based on an inverted rotating disc electrode for excitation by using a confocal Raman microscope. Furthermore, we developed a SER(R)S-active silver modified silver substrate for spectro-electrochemical applications. For this purpose silver nanoparticles (AgNPs) were adsorbed on top of a planar silver surface. The substrate was optimized for an excitation wavelength of 413 nm corresponding to the resonance frequency of heme structures. An enhancement factor of 10 5 was achieved. The high performance of the new measuring cell in combination with the new silver substrate was demonstrated using cc as a reference system.